2022
DOI: 10.1038/s41598-022-21173-9
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis on alcohol consumption and risk of endometriosis: an update from 2012

Abstract: Endometriosis is a complex and chronic disease, whose multifactorial nature has encouraged a deep investigation on the role of lifestyle factors. A strong association between alcohol intake and endometriosis risk has already been shown. We aimed to confirm this association, considering the updated literature. 23 eligible studies were identified through comprehensive literature search of PubMed and EMBASE (May 2012–October 2021). A borderline statistical significance was found comparing any alcohol consumption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 66 publications
0
4
0
2
Order By: Relevance
“…This result is partly in contrast with the literature evidence. In fact, a recent meta-analytic study found a positive association between alcohol intake and endometriosis, suggesting that alcohol could be considered on one hand a coping strategy for the management of several difficulties related to endometriosis, and, on the other hand, it could directly increase the risk of developing endometriosis through inflammatory mediators and oxidative stress [ 62 ]. Hence, based on these contradictory findings, it is only possible to suppose that alcohol intake is an indicator of women’s general QoL.…”
Section: Discussionmentioning
confidence: 99%
“…This result is partly in contrast with the literature evidence. In fact, a recent meta-analytic study found a positive association between alcohol intake and endometriosis, suggesting that alcohol could be considered on one hand a coping strategy for the management of several difficulties related to endometriosis, and, on the other hand, it could directly increase the risk of developing endometriosis through inflammatory mediators and oxidative stress [ 62 ]. Hence, based on these contradictory findings, it is only possible to suppose that alcohol intake is an indicator of women’s general QoL.…”
Section: Discussionmentioning
confidence: 99%
“…amount of alcohol intake and endometriosis [84,95] Further, two meta-analyses performed by the same group looked at alcohol intake and endometriosis based on the literature available in 2012 and 2021 [96,97]. Their findings initially suggested an association between endometriosis and alcohol with a summary estimate OR of 1.24 (95% CI: 1.12, 1.36) [96].…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%
“…However, several other case-control and cohort studies have concluded that there may not be a significant association [ 82 , 83 ]. Interestingly, one prospective cohort study of over 1700 individuals and a smaller observational study showed an inverse relationship between the amount of alcohol intake and endometriosis [ 84 , 95 ] Further, two meta-analyses performed by the same group looked at alcohol intake and endometriosis based on the literature available in 2012 and 2021 [ 96 , 97 ]. Their findings initially suggested an association between endometriosis and alcohol with a summary estimate OR of 1.24 (95% CI: 1.12, 1.36) [ 96 ].…”
Section: Endometriosismentioning
confidence: 99%
“…Asociaciones alimentarias: el mayor consumo de carne roja se asoció con un aumento del riesgo de https://doi.org/10.55204/scc.v2i2.e24 endometriosis (RR 1.17), al igual un mayor consumo de ácidos grasos trans (RR 1.12) y un mayor consumo de ácidos grasos saturados (RR 1.06) (46). Estilo de vida: el consumo de alcohol en general comparado con no consumo mostró una significancia estadística (RR 1.25 y OR 1.14) (47,48) y el consumo moderado de alcohol se relación de igual manera con riesgo de endometriosis (OR 1.22) (48). En la exposición a alteradores endocrinos: de manera general ofrecen un 41% mayor riesgo de endometriosis (RR: 1.41) (47), además, se identificó que los bifenilos policlorados (PCBs) tuvieron un aumento consistente en el riesgo (OR 1.58), seguido de los plaguicidas organoclorados (OCPs) (OR 1.40), esteres de Ftalato (PAEs) (OR 1.27), en el subgrupo de di-(2-etilhexil)-ftalato (DEHP) (OR 1.42) (tabla 1) (49) Carnes y Ácidos Grasos: Mayor consumo de carne roja se asoció con un aumento del riesgo de endometriosis (RR 1.17; 95% IC, 1.08 a 1.26; p < 0.001; I2 = 82.4%).…”
Section: Tecnología De Reproducción Asistida (Tra)unclassified
“…Las tasas de embarazo clínico (OR = 0.83; IC 95% = 0.66 a 1.05, p = 0.86), el número de óvulos maduros recuperados y las tasas de aborto no fueron estadísticamente diferentes entre los grupos de estudio. Sin embargo, el número total de óvulos recuperados fue menor en el grupo de cirugía (diferencia media = -1.51; IC del 95% = -2.60 a -0.43, p = 0.02) Abreviaturas: DIE: endometriosis infiltrante profunda, FIV: la fecundación in vitro, hMG: gonadotrofina humana, GnRH: hormona liberadora de gonadotrofina, HOC: hiperestimulación ovárica controlada, FIV/ICSI-ET: fecundación in vitro/inyección intracitoplasmática de espermatozoides-transferencia de embriones, MTC: medicina tradicional china, OR: Odds ratio, IC: intervalo de confianza Realizado por: María Guaman En la revisión exhaustiva de estudios observacionales y metaanálisis de Zhang et al (47) y Li et al (48), se evaluaron alrededor de 40 factores de riesgo ambientales en relación con la endometriosis. Estos factores incluyeron elementos relacionados con el estilo de vida, factores reproductivos, exposiciones tempranas en la vida, raza/etnia, y otros.…”
Section: éXito De Tratamiento Para Abordar La Infertilidad Asociada A...unclassified